Effect of Orbicularis Muscle Resection during Blepharoplasty on the Position of the Eyebrow - Patrocinio, Tomas G.; Patrocinio, Lucas G.; Patrocinio, Jose A. (Facial Plastic Surgery, 2018)
Dermatochalasis is a skin excess in the upper eyelid which may be associated with either an aesthetic and functional defect, blocking the peripheral vision. Upper blepharoplasty is the gold standard procedure for correction of dermatochalasis and to restore youthful contours to the periorbita. It is one of the most commonly performed procedures in aesthetic plastic surgery; however, there is still a lack of consensus about this procedure. The excess skin is sometimes removed alone or in conjunction with a strip of orbicularis oculi muscle. The rationale for both muscle and skin resection or skin alone preserving the muscle is uncertain. Some authors have studied the aging influence in brow position, and a few studies pointed out the influence of the upper blepharoplasty on brow height. The true effects, regarding the position of the eyebrow, of both techniques, with or without resection of the preseptal orbicularis oculi muscle, are unclear. The authors present a review of the literature to find the rationale for resecting or preserving the orbicularis oculi muscle in upper eyelid blepharoplasty and its relation to eyebrow position.
Keywords: eyebrow; blepharoplasty; orbicularis oculi muscle